Pembinaan Kepada Pemuda Gereja Baptis Jemaat Syalom Menyadari Pentingnya Akan Ibadah - Setulus Hati Laia; Ronaully Marbun (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The Shalom Baptist Church in Central Papua, specifically in Nabire, is where the Community Service Program (PKM) is being implemented. Based on observations of the youth of the Shalom Baptist Church, the community service team observed a lack of involvement in youth worship at church. This is due to several factors, including the increasing use of gadgets, which often influence today's youth, especially those of the Shalom Baptist Church, to the point of neglecting the youth worship service held at church. Therefore, the community service team took steps to address this issue by conducting guidance and a community service (KKR) to build the spirituality of the youth of the Baptist Church. The goal of this PKM is for the youth of the Baptist Church, particularly the Shalom congregation, to realize the importance of worship in their spiritual lives. In this paper, the community service team used observation, mentoring, discussion, and a survey. The results of this guidance and KKR showed that the youth of the Shalom Baptist Church experienced a self-awareness that worship is important